Danglers in patient information leaflets and technical manuals: an issue for specialised translators? - Henrik Køhler Simonsen (JoSTrans: The Journal of Specialised Translation)
Dangling participles and other types of ambiguous or unclear sentence constructions in directive and informative medical and technical texts, such as patient information leaflets (PILs) and technical manuals, render instructions unclear and potentially dangerous for the layman reader, i.e. a patient or a layman user of air condition units. Dangling constructions also constitute a constant challenge for translators with English as their second or third language. The objective of this article is to discuss dangling constructions with special emphasis on grammaticality, acceptability, and readability on the basis of two corpora: a corpus of PILs (PILcorp) and a corpus of technical manuals (TECHcorp). The hypothesis is that patient information leaflets will contain fewer dangling constructions than technical manuals because of the strict regulations on product information texts including PILs. The two corpora are analysed and categorised by means of selected theoretical considerations on dangling constructions, and selected examples from the two corpora are analysed by means of a Readability Test Tool (see Simpson 2012), which produces a number of readability indicators. This hypothesis has in fact been proved. The analysis and the discussion showed that dangling participles are not very frequent in PILs, but much more common in technical manuals. The data showed that there were no "ludicrous" danglers,(see Matthews and Matthews 2008:146), in PILcorp. However, the analysis showed that both corpora contained a number of dangling constructions, which may pose a cognitive problem for patients or laymen users because they necessitate considerable personal assumption and satisfactory reading proficiency.